Ascariasis in South Asia: Major Manifestations of Surgical Importance (The Journal of Ad-din Women's Medical College, 2023)
Introduction: Since a quarter of world’s population reportedly affected by Ascariasis round worm being endemic in south east Asian subcontinent like gangetic plain of Bangladesh, West Bengal, Kashmere valley etc. Biliary ascaiasis is one of the manifestation of round worm infestation.Objective: We conducted this retrospective study based on literature review available over the mid 2000 using the search key biliary Ascariasis, Biliary colic, Acute cholecystitis, obstructive jaundice, cholangitis, pancreatitis, hepatolithiasis, liver abscess. The search engine used was: Pubmed, Google Schoalr, HINARI, Embase and Scopus. We searched literature published from both endemic and non endemic area and aimed to study different types of clinical presentation, diagnostic tool, complications and their frequency and various treatment option for the management of biliary ascariasis. Result: Biliary colic is the commonest symptom. Acute cholecystitis, obstructive jaundice, cholangitis, pancreatitis, hepatolithiasis, liver abscess are other mode of presentation. Ultrasonography was reported to be an excellent non –invasive investigation for proper diagnosis and follows up in such conditions. Majority of cases are treated conservatively. ERCP (Endoscopic Retrograde Cholangio Pancreatography) based extraction of Ascaris lubricoids is possible in most of the situation where expert endoscopy services are available. Conclusion: Open common bile duct exploration and removal of worm is necessary in absence of endoscopy .Improvement of personal hygiene, improvement of sanitation and regular anti-helminthic administration can reduce these dreadful consequences of infestation by worms.The Journal of Ad-din Women's Medical College; Vol. 10 (2), July 2022; p 52-55